PERAN GURU TERHADAP KEAKTIFAN SISWA MELAKSANKAN SHALAT FARDHU DAN SHALAT SUNNAH ‘DHUHA’ - Alif 'Aini Sya’adah; Anwar Sa’dullah; Ibnu Jazari (VICRATINA, 2019)
The purpose of this study is to find out the role of the teacher in the activity of students in performing fard prayer and sunnah dhuha prayer. The problem faced is that there are still many students who have not been able to pray well, or students who intentionally ignore their prayers, with certain reasons such as better playing, going to the market, or just eating. Data sources were obtained from the principal, teacher and several students. This study uses qualitative methods, while the collection of document data obtained through interviews, observation, and documentation. And analyzed by document reduction, document presentation, drawing conclusions and verifying conclusions. The results of this study indicate that teacher development in the character of students is directed to reflect on what things can be obtained in prayer, especially the duha prayer. In addition to discussing that, the teacher usually makes a cult to discuss matters about religion so that students get a strong Islamic character in themselves.